The Right to Asylum between Islamic Shar'iah and International Refugee Law - Abou-El-Wafa Ahmed (AICTS, shahat Mansour, Cairo - Egypt, 2009)
The Right to Asylum between Islamic Shar'iah and International Refugee Law